Problematic questions in the development of specific prevention of dengue fever - E. I. Kazachinskaia; D. V. Shanshin; D. N. Scherbakov; A. M. Shestopalov (Медицинская иммунология, 2022)
Dengue fever known from literary sources since the Qin dynasty (265-420) is caused in humans when bitten by Aedes mosquitoes infected with the dengue virus (DENV) and manifests as a flu-like disease. A feverish state can be accompanied by dyspeptic disorders (nausea, vomiting, diarrhea) and a rash. Approximately 1-2% of infections are clinically presented as the most severe form – it is dengue hemorrhagic fever/dengue shock syndrome (DHF/DSS) leading to 500 thousand annual hospitalizations with a mortality rate of about 5% in endemic areas.Four genetically removed DENV serotypes (1, 2, 3, and 4) are classified as different types of viruses within the same antigen complex and have almost identical epidemiological features. In 2013 a new serotype DENV-5 was isolated.Until the 1980s in most geographical regions of the world where dengue fever was registered only one or two viral serotypes were detected as an etiological agent of the disease. Over time there is an increase in the cocirculation of four types of viruses which can serve as a key indicator of their global spread. As the “traces” of the four DENV species overlap more and more the threat of severe disease increases due to the phenomenon of antibody-dependent of infection when re-infected with a heterologous viral serotype.Development of specific dengue fever prevention has been underway since 1944 (since the discovery of viral agents of this disease) but the first and so far only licensed in 2015 tetravalent vaccine-Dengvaxia developed by the French pharmaceutical company Sanofi Pasteur has been effective in varying degrees of protection against infection with each of the viral serotypes and in addition dangerous for previously seronegative people. Research aimed at obtaining a safe and effective vaccine is continuing. Neutralizing monoclonal antibodies are a necessary tool for studying the antigenic structure of viral immunogens as base of prevention preparates against dengue fever.